Нейронні мережі як засіб прогнозування значення температури за перехідним процесом - Лопатко, Ольга; Микитин, Ігор (Видавництво Львівської політехніки, 2016)
Проаналізовано нейронні мережі як засіб прогнозування значення температури за перехідним процесом. Розглянуто штучний нейрон як основу нейронної мережі. Наведено класифікацію нейронів залежно від функцій, які вони виконують в нейронній мережі, та основні види передавальних функцій нейрона. Подано класифікацію нейронних мереж за критерієм їх архітектури, алгоритму навчання та типу завдань, які вони можуть виконувати. Зроблено висновок, що для розв’язання поставленої задачі оптимальним є застосування нейронної мережі з архітектурою прямого поширення з алгоритмом навчання з вчителем. Проанализированы нейронные сети как средства прогнозирования значения температуры за переходным процессом. Рассмотрен искусственный нейрон как основа нейронной сети. Приводится классификация нейронов в зависимости от функций, которые они выполняют в нейронной сети, и основные виды передаточных функций нейрона. Представлена классификация нейронных сетей по критерию их архитектуры, алгоритма обучения и типа задач, которые они могут выполнять. Сделан вывод, что для решения поставленной задачи оптимальным является применение нейронной сети с архитектурой прямого распространения с алгоритмом обучения с учителем. The present article considers neural networks as a tool for the temperature prediction using transition process. The authors emphasize the need to measure high temperatures in technological processes and indicate problems encountered on this way. The method proposed to solve this problem is neural networks application. The study of artificial neural networks is motivated by their similarity to successfully working biological systems, which – in comparison to the overall system – consist of very simple but numerous nerve cells that work massively in parallel and (which is probably one of the most significant aspects) have the capability to learn. There is no need to explicitly program a neural network. One result from this learning procedure is the capability of neural networks to generalize and associate data: after successful training a neural network can find reasonable solutions for similar problems of the same class that were not explicitly trained. This in turn results in a high degree of fault tolerance against noisy input data. At the very beginning the authors describe artificial neuron as a basis of a neural network and provide its block diagram. Neurons classification depending on the functions they perform in the neural network is also present. They also defined the transfer function of the artificial neuron and its basic types (linear transfer function, positive linear transfer function, piecewise linear transfer function, step transfer function and logistic transfer function) alongside with mathematical expressions (formulas) and diagrams that describe neural networks behavior. Then, the authors present a neural networks classification based on their architecture (feedforward neural networks, recurrent neural networks and completely linked neural networks were specially highlighted). Each type of these was provided with detailed drawings and structures explanation. In addition, the present article includes a neural network classification, based on training algorithm and the type of problem that such neural network is able to perform. At the end of the article the authors make conclusions about the most relevant neural network architecture in case of temperature prediction problem using transition process and consider the corresponding learning algorithm. Plans for further research were also outlined.
Keywords: нейронна мережа; прогнозування значення температури; температурний перехідний процес; нейронная сеть; прогнозирование значения температуры; температурный переходный процесс; neural network; temperature prediction; temperature transition process; 536.531(2)